VO2 assessed by backward extrapolation in 200, 400, 800 und 1500 m front crawl in youth swimmer - Zacca, R.; Lopes, A. L.; Teixeira, B. C.; de Matos, C. C.; Engelmann, L.; de Souza Castro, F. A. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The aim of this study was to compare oxygen consumption (V0 2 ) responses assessed by backward extrapolation after 200, 400, 800 and 1500 m in youth swimmers. V02 in the 400 m was greater than all other distances, with enough time and intensity for the swimmers to achieve V02max at the end of the 400 m maximal effort. Although less accurate and precise, backward extrapolation technique was confirmed to be attractive and able to identify similar V02 values to those obtained during swimming with direct assessment methods.